Evaluation of the mechanical properties of concrete by incorporating aloe vera extract as a carbonation rust inhibitor (Gaceta Técnica, 2025)
The objective of the study was to evaluate the incidence of aloe vera extract as an inhibitor of carbonation-induced rust in concrete. Likewise, the study adopted an applied methodology and an experimental design, in which concrete was evaluated with different dosages of aloe vera extract in which the concentrations used for the incorporation of aloe vera in the concrete were 0,75%, 1,30% and 1,7%. In addition, the results indicate that the incorporation of aloe vera in concrete differently affects its properties, depending on the concentration. It was highlighted that at low concentrations of 0,75%, a slight increase in the carbonated zone and a slight improvement in compressive strength (5%) were observed, without significantly altering the consistency or flexural strength. However, at higher concentrations such as 1,30% and 1,70%, the effects were minor or even negative, suggesting that an excess of aloe vera could negatively affect the structure of the concrete